Mother Chemical Stimulus and Aggregation Behaviour of Tadpoles in a Neotropical Foam‐Nesting Frog - Carrillo, Juan F. C.; Ortega, Zaida; Santana, Diego J.; Prado, Cynthia P. A. [UNESP] (Wiley, 2025)
ABSTRACT Aggregation behaviour is a common strategy among aquatic organisms to avoid predators and may result from social interactions mediated by signals and/or cues. Tadpoles of some species in the Neotropical genus Leptodactylus (Leptodactylidae) exhibit schooling behaviour and are escorted by an attending female. Here, we experimentally tested whether chemical skin secretion produced by attending females of Leptodactylus macrosternum triggers tadpole schooling behaviour. We assessed aggregation time of the tadpoles of L. macrosternum under three different chemical stimuli—male, non‐attending female and attending female—and compared it to a control. We found that tadpoles only increased the time of aggregation under the presence of the chemical stimulus of the attending females. Tadpoles of other species from the L. latrans group, such as L. insularum and L. luctator , may present similar responses to the attending female chemical stimulus. The next steps would be to identify the chemical components used as signals or cues and to conduct additional behavioural experiments to better assess intra‐ and interspecific communication between tadpoles and attending females.